ZnO Nano Particles (NPs) Properties Prepared by Liquid Phase Laser Ablation (LPLA) - Hassoon, Khaleel I; Sabeeh, Sabah H; Khalaf, Mustafa A (Al-Nahrain Journal of Science, 2017)
In this work a ZnO NPs have been prepared by liquid phase laser ablation technique from Zn target immersed in ethanol solution. The effect of laser energy and the number of laser pulses of LPLA technique which includes the optical, morphological and structural measurement were investigated. The XRD measurements confirm the presence of ZnO nano size and particle size of average of 41 nm; this has good agreement with TEM measurement. The optical measurements show the increases in the number of the laser pulses as well as increase the laser energy lead to increase the energy band gap, however the absorptions peaks appears to be at the average of 298 nm which yield an energy band gap of 3.5 eV.